PEMBACAAN SIMBOL-SIMBOL KESEDERHANAAN DALAM FILM PENDEK: "ANTARA JOKO WIDODO, PRABOWO, DAN SETYO NOVANTO" DALAM CHANNEL YOUTUBE NAJWA SHIHAB - Asriadi (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This study aims to describe social criticism of the short film by dr. Tompi entitled "Between Joko Widodo, Prabowo, and Setya Novanto" which was broadcast on the YouTube channel Najwa Shihab. The research approach used Roland Barthes' semiotic analysis by reading the symbols that appear in the short film. The results show that the symbols of simplicity shown by the figures in the film convey a message that luxury symbolized by the place where a person eats is not always attached to the characters who are displayed and liked by the community. The mingling of the character with the community shows that there is no class difference between the character and the community. The forms of symbols that appear include voice and facial expressions depicting messages that have a meaning behind them and have a clear meaning of the message.